Textural quality attributes of gluten-free batter and bread as affected by hydrocolloids - Encina-Zelada, Christian René (2019)
This study aimed to compare the separate effects of xanthan gum (XG), guar gum (GG) and hydroxyl-propyl methyl-cellulose (HPMC) on gluten-free batter and bread quality; and to explore the interrelationships among 24 measurements of physicochemical and rheological attributes of batter and bread. Twenty-seven formulations were produced with 1. 5, 2. 5, 3.5% XG and 90, 100, 110% water (9 combinations); 2. 5, 3. 0, 3. 5% GG and 90, 100, 110% water (9 combinations); and 3.0, 4.0, 5.0% of HPMC and 80, 90, 100% water (9 combinations). A principal component analysis reveated that the information contained in the 24 variables could be effectivety decomposed into two major components, one related to bread crumb porosity and hardness (45%), and the other to batter viscosity (32%). XG and GG produced gluten-free batter and bread of similar quality, although GG, particularly at high dose, can produce smaller loaves of harder and more resilient and cohesive crumb than XG. Compared to XG and GG, HPMC yielded batters of higher stickiness, consistency and firmness, which, when baked, produced loaves of higher volume, softer crumb, and larger pores.